Peran Profitabilitas, Likuiditas, dan Leverage Terhadap Internet Financial Reporting Studi Perusahaan Manufaktur yang terdaftar pada BEI - Rachmah, Nur Maulidah; Prapanca, Detak; Hariasih, Misti (Universitas Islam Kadiri, 2024)
The aim of this research is to find out the Profitability, Liquidity and Leverage of Internet Financial Reporting in the Study of Manufacturing Companies listed on the IDX. The method used is quantitative research, or data-based studies that will be examined statistically. Data collection in this research applies an archival approach, where data is collected based on information that is already available in existing databases. This research uses two types of variables, namely independent and dependent variables. Internet Financial Reporting is the dependent variable of the research. Meanwhile, Profitability (X1), Liquidity (X2), and Leverage (X3) are independent factors. The results of investigations and debates using the SPSS program application, the findings of this research conclude that 1) Profitability influences Internet Financial Reporting. 2) Liquidity influences Internet Financial Reporting, and 3) Leverage influences Internet Financial Reporting